Paederus beetles: the agent of human dermatitis - Shabab Nasir; Waseem Akram; Rashad Rasool Khan; Muhammad Arshad; Iram Nasir (Journal of Venomous Animals and Toxins including Tropical Diseases, 2015)
Background Rove beetles of the genus Paederus cause dermatitis when they come in contact with human skin. This condition is prevalent in some tropical and subtropical regions, such as in northern Pakistan, where it was recorded for the first time by US troops. Despite much research from other countries on this subject, few studies, mostly clinical, have been performed in a Pakistani context. A survey was carried out in villages, towns and cities of Punjab province, Pakistan, to explore the rove beetle population dynamics and to develop a model to elucidate the symptoms, preventive measures and treatment strategies for this dermatitis. Methods The prospective observational and patient surveys were performed bimonthly over a period of two years, in different districts of Punjab province. Collection was carried out in fields, gardens and houses during every visit with the aid of a pitfall trap, light trap, flight intercept trap, Berlese funnel trap and sweep netting. These traps were installed for four days during every visit. Interviews of ten individuals of different ages and sexes from each site were recorded during each visit. Results Out of 980 individuals, 26.4% were found to suffer from Paederus dermatitis. Lesions were most commonly found on the neck followed by the face. In July-August during the rainy season, this skin irritation was most prevalent and the population of these beetles peaked (36.2%). During May-June, the beetle population was lowest (7.85%) due to soil dryness. About 70% of such irritation cases were from individuals living in farming villages or in farmhouses. Their houses typically (80%) had broken doors and screen-less windows while 97% of the residents were unaware of how they may have come into contact with these beetles. In most cases (91% from villages/small towns and 24% from cities and adjoining areas) the local residents were unaware of modern treatment strategies. Conclusions Paederus dermatitis is extremely frequent in villages with poor housing facilities and could be avoided via community awareness.